2013
DOI: 10.1002/j.0022-0337.2013.77.10.tb05600.x
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions About the Mission of Dental Schools to Advance Global Dentistry and Philanthropy

Abstract: In this study, 491 dental students at one dental school in the United States and one in Bulgaria were surveyed to assess their perceptions about the mission of dental schools to advance global dentistry and philanthropy. The study included questions about prior involvement in charitable dental missions. Many respondents felt that their dental school does not advance global dentistry nor adequately teaches students the virtues of philanthropy and volunteerism. The majority agreed, however, that dental schools h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…The results concur with the survey conducted among American (95.8%) and Bulgarian (81.5%) students. 7 However, only half of the students surveyed at KSUCD thought that KSUCD’s mission statement emphasized teaching students to have compassion, nor promoted volunteerism (57.1%) in comparison with American (84.5%) and Bulgarian students (88.0%). This may indicate that the students perceived a need to specifically include these goals in KSUCD’s mission statement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results concur with the survey conducted among American (95.8%) and Bulgarian (81.5%) students. 7 However, only half of the students surveyed at KSUCD thought that KSUCD’s mission statement emphasized teaching students to have compassion, nor promoted volunteerism (57.1%) in comparison with American (84.5%) and Bulgarian students (88.0%). This may indicate that the students perceived a need to specifically include these goals in KSUCD’s mission statement.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that the students perceived a need to specifically include these goals in KSUCD’s mission statement. Students in general (86% Saudi, (83%) American, and 77.2% Bulgarian) 7 feel that it is a moral duty of their dental school to provide oral health care to those who lack access to equitable health care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dental schools play a vital role in the improvement of oral health care worldwide, and reports have suggested that students believe dental schools have a moral obligation to address global oral health inequities 12,13 . Dental schools are responding to both growing need and student demand by providing a variety of global health experiences.…”
mentioning
confidence: 99%